A STUDY OF THE ORIENTATION DEPENDENCE OF THE CU-63 NUCLEAR-MAGNETIC-RESONANCE IN THE (TL0.5PB0.5)SR-2(CA1-YYY)CU2O7-DELTA SYSTEM - Dai, G; Tunstall, D; Liu, R; Edwards, P (Elsevier, 1994)
Nuclear magnetic resonance (NMR) results for copper-63 nuclei in the Tl-based 1212 system (Tl0.5Pb0.5)Sr2(Ca1-yYy) Cu2O7-δ (0.0 ≤ y ≤ 0.8) are reviewed. We report the NMR spectra both on random powder samples and partially aligned powder samples. After deconvoluting the random fraction from the partially aligned spectra, we obtain the resonance frequency as a function of θ, the angle between c-axis and the applied magnetic field B. Using the theoretical equation to fit the experimental data, we calculate the isotropic Knight shift, Kiso, the axial Knight shift, Kax, and the quadrupole resonance frequency vQ for each value of y (0 ≤ y≤ 0.8). Nuclear quadrupole resonance (NQR) on the y=0.0 sample was performed. The measured quadrupole resonance frequency is in very good agreement with the result from the NMR experimental data. We correlate these dependences on y of the resonance parameters with other structural trends.